MENINGKATKAN MANAJEMEN TOKO KELONTONG DALAM MENGHADAPI RITEL MODERN DI DESA MENGWI KABUPATEN BADUNG - Seminari, N.K.; Purnawati, N.K.; Artini, L.G.S.; Rastini, N.M.; Nurcaya, I.N.; Warmika, I.G.K. (Buletin Udayana Mengabdi, 2018)
Modern retail like Alfamart and Indomaret develops really fast at some cities in Indonesia. These retails has a strong management which is a network. In some region this things are considered “threats” to the grocery store or either a small mini-market. One of the problems of this kinds that is being observed is in Mengwi Village Mengwi Sub-district Badung Regency. Seeing this condition then a community service is held which entitled “Increasing the Management of Grocery Store in Order to Face Modern Retail in Mengwi Village Mengwi Sub-district Badung Regency. The purpose of this community service is to increase the management of Grocery Store in order to face the threats of modern retail such as Alfamart and Indomaret. The coaching will be held by visiting one kind of grocery store or mini-market that located in Mengwi Village. The amount of traders that are coached are 40 people. This community service formally held within 5-7 days, this activity is expected to be able reach the traders generally. The result of the community service is expected to be able to arrange the financial administration, the product’s turnover, product’s arrangement, the change of the price’s information, and a better consumer service. For the community service’s team, this activity is useful to apply theories and devoted themselves to the people.